Additive interaction of pre-pregnancy BMI and assisted reproductive technology on the risk of pregnancy-induced hypertension - Liting Wu; Feifei Chen; Miaomiao Chen; Yaping Hu; Ying Wang (Gynecological Endocrinology, 2024)
Objective To explore the combined effect of pre-pregnancy body mass index (BMI) and assisted reproductive technology (ART) on the risk of pregnancy-induced hypertension (PIH).Methods This retrospective cohort study included 3,220,103 women with singleton pregnancies from the National Vital Statistics System database for 2021. The outcome was the occurrence of PIH. Logistic regression analyses were utilized to assess the association between pre-pregnancy BMI and ART and PIH. To evaluate the interaction of pre-pregnancy BMI and ART on PIH, the relative excess risk of interaction (RERI), the attributable proportion due to interaction (API), and synergy index (SI) were applied.Results Of these 3,220,103 women, 302,789 [9.40% (95%CI: 9.37%-9.43%)] occurred PIH. Women with a pre-pregnancy BMI ≥25 kg/m2 [odds ratio (OR)=2.06, 95% confidence interval (CI): 2.04-2.08] or using ART (OR = 1.43, 95%CI: 1.39-1.47) were related to a higher risk of PIH. There was a positive additive interaction of pre-pregnancy BMI and ART on the risk of PIH, with an interaction RERI, API, and SI of 0.20 (95%CI: 0.08-0.33), 0.07 (95%CI: 0.03-0.11), and 1.13 (95%CI: 1.05-1.21), respectively. Stratified analyses demonstrated that the positive additive interactions of pre-pregnancy BMI and ART on PIH were observed in women aged <35 years or ≥35 years and in women with unipara or multipara, whereas only in White women.Conclusion A positive additive interaction of pre-pregnancy BMI and ART on the risk of PIH was found, with an interaction of 7%.